The Bioprospecting of Anti-Vibrio Streptomyces species: Prevalence and Applications - Loh Teng-Hern Tan; Learn-Han Lee; Bey-Hing Goh (Progress in Microbes and Molecular Biology)
Vibrio sp. has been a major pathogen that resulted in difficult to treat infections, and greatly impacting the aquaculture industry. Thus, more effective approaches are needed to overcome this problem. Bacteria of the genus Streptomyces is a group of prolific producers for various bioactive compounds. Streptomyces species with antibacterial activity against Vibrio sp. have been reported from numerous studies, indicating that Streptomyces could be a good candidate for treatment of Vibrio infections. This review aims to provide an overview on the distribution of the Streptomyces with anti-Vibrio activity from diverse geographical locations. Furthermore, this review also highlighted that Streptomyces sp. can be a great source for anti-Vibrio agents to control vibriosis, such as in the aquaculture settings.